(untitled) (Sains Humanika, 2014)
This study intends to compare quality of teacher’s working life among teachers in three types of primary schools, namely national-type school (SK), Tamil Vernacular School (SJKT), and Chinese Vernacular School (SJKC). In this study, working life quality of teachers was conceptualised from four dimensions of needs: (a) Psychological needs; (b) Social needs; (c) Political needs; and (d) Economical needs. Questionnaire was administered to a total of 1080 teachers. The samples were selected from 90 primary schools in Penang and southern Kedah. The comparison of domain score of quality of teacher’s working life was done across the three types of schools using one-way variance analysis (ANOVA) after establishing item calibration for each dimension of working life quality of teachers using Rasch Measurement Model. Findings showed teachers in SJK(T) had high scores for each dimension of working life quality followed by teachers in SK and SJK(C). In the final part of the study, implications on knowledge and organisational practice were discussed.